2015
DOI: 10.1210/jc.2014-2439
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mass in Young Adulthood Following Gonadotropin-Releasing Hormone Analog Treatment and Cross-Sex Hormone Treatment in Adolescents With Gender Dysphoria

Abstract: Between the start of GnRHa and age 22 years the lumbar areal BMD z score (for natal sex) in transwomen decreased significantly from -0.8 to -1.4 and in transmen there was a trend for decrease from 0.2 to -0.3. This suggests that the BMD was below their pretreatment potential and either attainment of peak bone mass has been delayed or peak bone mass itself is attenuated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
174
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(201 citation statements)
references
References 22 publications
10
174
0
2
Order By: Relevance
“…This decrease is probably related to a change in growth velocity and lower bone mineral accrual, which are known determinants of alkaline phosphatase levels, 28 because we observed a decrease in height SDS and GnRHa treatment has been shown to result in a decrease in bone mineral density z-scores. 21 This study has some weaknesses. First, the number of adolescents who presented in early puberty was small, which made it difficult to assess whether early pubertal changes regress under GnRHa treatment and whether prolonged puberty suppression is safe.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This decrease is probably related to a change in growth velocity and lower bone mineral accrual, which are known determinants of alkaline phosphatase levels, 28 because we observed a decrease in height SDS and GnRHa treatment has been shown to result in a decrease in bone mineral density z-scores. 21 This study has some weaknesses. First, the number of adolescents who presented in early puberty was small, which made it difficult to assess whether early pubertal changes regress under GnRHa treatment and whether prolonged puberty suppression is safe.…”
Section: Discussionmentioning
confidence: 96%
“…21 From a combined analysis of several studies in children with CPP, it was concluded that long-term GnRHa treatment does not seem to cause an increase in BMI SDS. 6 We observed an increase in fat percentage and decrease in lean body mass percentage in boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…Although puberty suppression has a positive effect on psychological functioning for many adolescents [20] and is fully reversible (since puberty reinitiates when treatment is stopped), and although adverse events have not been reported in evaluation studies [21][22][23], iatrogenic risks have to be taken into account. It has been shown that GnRHa treatment influences bone mass development in delaying peak bone mass accrual [23] and that it may cause hypertension (especially in birth-assigned girls) [24]. Adolescents are therefore advised to maintain a healthy lifestyle through appropriate weight maintenance, sufficient weight-bearing exercise, and adequate calcium and vitamin D intake [25].…”
Section: To Treat or Not To Treat?mentioning
confidence: 99%
“…The current SOC guidelines do not set strict age criteria for the start of either intervention [10]. This is somewhat remarkable since the only scientific evidence of the psychological efficacy [20,31] and medical efficacy and safety [21][22][23][24]32] of the treatment is based on the "Dutch protocol" as it was introduced. At that time, the protocol set strict minimum age criteria for starting puberty suppression (12 years of age), cross-sex hormone treatment (16 years of age), and gender-affirming surgeries (18 years of age) [33].…”
Section: What About Age?mentioning
confidence: 99%
“…Known risk factors for osteoporosis include underutilization of hormones after gonadectomy or use of androgen blockers without or with insufficient oestrogen [31]. GnRH agonists also may result in short-term decline in BMD [60].…”
Section: Comorbidities and Other Considerationsmentioning
confidence: 99%